The Elusive Cases of Carrier Females and G6PD Deficiency - Khan, Zahra Rashid; Shaheen, Nasira; Ali, Nadir (International Journal of Pathology, 2018)
Objective: To screen newborn population for G6PD deficiency and compare results of the Dye ReductionTest (DRT) with Quantitative estimation of G6PD deficiency.Study Design: Cross-sectional study at Haematology Department, Army Medical College, NationalUniversity of Sciences and Technology and Military Hospital, Rawalpindi, (January-August, 2011)Methodology: Cord blood (2.5 ml blood in K3EDTA bottle) samples were obtained from 120 newbornsafter informed consent from parents. 65 patients were males and 55, females. Samples were evaluatedfor G6PD deficiency using qualitative (DRT) and quantitative spectrophotometric technique. Data obtainedwas analyzed using SPSS Windows version 17.Results: Frequency of G6PD deficient cases was 2.5% by DRT and 4.2% by quantitative estimation.DRTmisclassified 2 cases of partial deficiency as normal in female population.Conclusion: DRT has a diagnostic accuracy of 98.3 %, is specific, cost effective and easy to perform.However, heterozygote female detection continues to be a challenge with this technique.